Design and Application of a Double-Inductor Boost Converter for Powertrain in Fuel Cell EVs - Torbacioglu, Goksen Ali; Bayrak, Gokay (Ieee, 2025)
The output voltage obtained from a fuel cell stack in Fuel Cell Electric Vehicles (FCEVs) constantly changes, and this variable output voltage must be converted to the appropriate voltage for power transmission in FCEVs. This study proposes a new double inductor DC-DC boost converter capable of adjusting the voltage from 25 to 48 V DC from a 1 kW fuel cell output to the 96 V DC level required for an FCEV powertrain system. First, the design and analysis of the proposed double inductor DC-DC boost converter are performed. Then, the designed converter is also experimentally implemented and compared with the results obtained mathematically. The obtained results show that the proposed converter is applicable in practice with an efficiency of 92.3%. It is thought that this structure, which can be used in practice in power transmission applications in FCEVs, can be used in many applications, especially in electric and hybrid energy vehicles, by increasing its power with scaling.
2025 International Conference on Smart Grid-ICSMARTGRID-Annual -- MAY 27-29, 2025 -- Glasgow, ENGLAND
Keywords: Fuel Cell; Electric Vehicle; Powertrain; Boost Converter; Double Inductor Topology